Rethinking ecotoxicological paradigms: microbial-mediated tolerance and life-history trade-offs of Folsomia candida in hydrocarbon-contaminated groundwater - Sara Remelli; Laura Ducci; Laura Filonzi; Riccardo Pinardi; Pietro Rizzo; Fulvio Celico; Emanuele Scanferla; Marcello Pianu; Cristina Menta (Chemosphere, 2026)

From wild to hatchery and back: How captive Mediterranean brown trout are impacting remnant populations of Salmo ghigii in Italy - Andrea Splendiani; Andrea Gandolfi; Tatiana Fioravanti; Tommaso Righi; Lorenzo Tancioni; Anna Rita Rossi; Gianluca Zuffi; Alessandro Marieni; Paolo Lo Conte; Michele Spairani; Francesco Nonnis Marzano; Laura Filonzi; et al. (Biological Conservation, 2026)

When art meets nature: understanding the historical distribution of European pikes - Elena Giannico; Lisa Chiavini; Mauro Natali; Federico Della Bina; Flavia Chiavoni; Leonardo Brustenga; Alessia Ardenghi; Laura Filonzi; Francesco Nonnis Marzano; Livia Lucentini (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)
In recent decades, new European pike species have been described, highlighting the invasion of Italy by a northern European taxon. Morphological and genetic data strongly support taxonomic differences between two separated ESUs (Evolutionary Significant Units), a northern and a southern taxon isolated by the alpine barrier. However, despite scientific advances, the historical occurrence of the northern European taxon in Italy prior to its recent expansion or introduction remains uncertain. This study analyzes iconographic representations of the genus Esox in European art, without the use of artificial intelligence tool, from the 13th to the twentieth century, to assess whether phenotypic differences depicted in artworks can provide insight into the historical distribution of northern and southern European pikes. Seventy-three out of 86 pictorial works (85%) depicting pikes allowed species-level attribution based on color patterns with proved taxonomic relevance described in the literature. The results reveal a strong association between depicted color patterns and the geographical and cultural background of the artists, suggesting the northern pike could have been absent in Italy before its documented introduction. Overall, by fostering interdisciplinary dialogue between art history and the natural sciences, this study highlights the potential of iconographic analysis as a complementary approach for investigating historical species distributions and providing additional evidence relevant to the study of biological invasions.

Integrating environmental DNA , diving surveys and DNA barcoding to track endangered twaite shad ( A losa fallax ) spawning sites - Alessia Ardenghi; Laura Filonzi; Nicolò Bellin; Pietro Maria Rontani; Matthew A. Campbell; Mattia Saccò; Morten E. Allentoft; Daniele Nizzoli; Armando Piccinini; Riccardo Papa; Francesco Nonnis Marzano (Journal of Fish Biology, 2026)
The twaite shad ( A. fallax ), an anadromous fish species belonging to the Clupeidae family, has experienced population declines throughout Europe. This decline is attributable to a range of anthropogenic pressures, including migration barriers, environmental pollution, habitat degradation, predation by invasive species and unsustainable fishing practices. These factors disrupt the species' lifecycle and ecological balance, leading to significant conservation concerns. Typically, spawning occurs from late spring to early summer, which is when the migration might be up to 400 km upstream from the sea. The demersal eggs hatch relatively quickly, and the larvae start a planktonic life in the river. Traditional monitoring methods have often proved inadequate due to the cryptic nature of A. fallax . With the goal of improving the efficacy of current biomonitoring designs, we tested an environmental DNA (eDNA) approach based on 12S rRNA gene Illumina sequencing to monitor A. fallax migration and spawning sites in the Po and Taro rivers in Northern Italy. This molecular approach was supplemented by scuba diving observations to visually confirm fish presence and habitat conditions at the same sites. Additionally, the collected larvae were morphologically identified and analysed with DNA barcoding to assess the correct taxonomic assignment of the species. This multi‐level framework confirmed the upstream migration and identified specific spawning sites, as well as the presence of larvae, highlighting the effectiveness of eDNA in detecting A. fallax populations. These findings underline the potential of eDNA as a powerful conservation tool for monitoring anadromous fish populations and guiding management strategies.

Conservation genetics of barbel species (Teleostei, Cyprinidae) facing hybridization and introgression along an elevational gradient in protected areas of northern Italy - Claudio Ferrari; Federica Piccoli; Andrea Voccia; Pietro Maria Rontani; Stefano Leonardi; Alessia Ardenghi; Francesco Nonnis Marzano; Laura Filonzi (Zoologica Scripta, 2025)
The European endemic barbels represent important bioindicators of river quality and are nowadays threatened by changing environmental conditions and hybridization with the invasive alien Barbus barbus . It is therefore fundamental to investigate interactions among species and adaptability to climate changes in protected areas of Northern Apennines. An investigation was carried out considering 248 barbel samples that were analysed for Cytb mitochondrial DNA and 192 at 10 microsatellite loci, to delineate the distribution and population structure of the two native species as well as the impact of invasive B. barbus inside 15 sites of the Natura 2000 network. The complex distribution of the native barbel species was highlighted, together with a significant genetic structure emerging in different populations. Only one site revealed a “pure” population of B. caninus while the other ones showed a high level of hybridization between the different barbel species. For the B. plebejus two “genetically pure” populations were found in the hill‐mountain sector, while the hybridization level resulted in increasing in the lowest altitudinal stretch of watercourses with a consistent contribution driven by B. barbus . We herein present the first evidence of B. barbus introgression along an altitudinal gradient, carried from the lowland water course to mountain stretches driven by B. plebejus migration. B. plebejus is the species that can act as vicariant organism able to transfer the B. barbus genome from the plain habitats into B. caninus genome of the higher altitude waterstreams, as a consequence of habitat shifts due to climate changes and anthropogenic acitivities.

First occurrence of a reproductive group of golden jackal (Canis aureus moreoticus) in a densely populated area south of the Po River (Italy) - Tiziano Travain; Emanuele Fior; Giulia Bigotti; Pier Luigi Fedele; Luca Lapini; Laura Filonzi; Paola Valsecchi; Francesco Nonnis Marzano (Mammal Research, 2024)

Genetic data on endangered twaite shad (Clupeidae) assessed in landlocked and anadromous populations: one or more species? - Stefania Chiesa; Armando Piccinini; Livia Lucentini; Laura Filonzi; Francesco Nonnis Marzano (Reviews in Fish Biology and Fisheries, 2014)